Spironolactone-induced gynecomastia: a case report - Ahamed, Shaik Khadeer; Thota, Sanjana Reddy; Dara, Deepthi; Tadikonda, Rama Rao (International Journal Of Community Medicine And Public Health, 2024)
The term "gynecomastia" refers to the benign growth of glandular breast tissue in men. In older men, adolescents, and newborns, physiological gynecomastia is common. Although it is self-limited, it can be managed to reduce both physical and emotional discomfort. Chronic conditions (such as cirrhosis, hypogonadism, and renal insufficiency), drug use (including prescription, over-the-counter, and illicit drugs), and tumors are rare causes of nonphysiologic gynecomastia. Exogenous estrogens, antiandrogens, 5-alpha reductase inhibitors, spironolactone, and cimetidine are the active ingredients that are known to cause gynecomastia the most frequently. A patient’s medical history is crucial in diagnosing drug-induced gynecomastia. Treating the underlying disease and stopping contributing medications are the cornerstones of treatment. In certain cases, gynecomastia can be treated with surgery and medications such as estrogen receptor modulators. Early intervention and patient-directed care are important aspects of treatment. We describe the pathogenetic mechanism of spironolactone-induced gynecomastia and provide a case report of a 52-year-old male patient.